EXPLORING THE RELATIONSHIP BETWEEN COMMUNICATION, WORK CULTURE, ORGANIZATIONAL COMMITMENT, AND MOTIVATION ON EMPLOYEE PERFORMANCE AT KRAMAT COMMUNITY HEALTH CENTER - Yoga Rizki Ramadhani; Cucu Herawati; A.D.Achmad (PT. Berkah Digital Teknologi, 2023)
Purpose of the study — To test and find out the causal relationship of several factors that influence employee performanceResearch method— This research is a quantitative research with regression. The population in this study were employees of the Kramat Community Health Center, Tegal Regency, Central Java Province, with a total of 68 employees. Data was collected by questionnaire and document study, after which the data was tested for validity and reliability.Result— The results of the study show that Communication, Work Culture, Organizational Commitment and Motivation affect Employee Performance simultaneously. The coefficient of multiple determination in this study uses the adjusted R square value because the independent variables in this study are more than 2 in estimating the effect of the two independent variables studied. From the data the adjusted R Square value is 0.598, this means that together the influence of the variables X1, X2, X3, X4 is 59.8% on the Y variable or in other words the influence of the independent variables (Communication, Work Culture, Organizational Commitment and Motivation) to the dependent variable (Performance) of 59.8% while the remaining 40.2% is caused by other variables that are not included in the research frameworkConclusion— Communication, Work Culture, Organizational Commitment, and Motivation have a significant effect on Employee Performance. The adjusted R-squared value of 0.598 indicates that these variables explain 59.8% of the variation in performance. Practical implications of the study include the importance of organizations focusing on improving communication, work culture, organizational commitment, and motivation to enhance employee performance. Social implications include the potential for improved productivity and job satisfaction in the workforce.